Radio transients from compact objects across the mass spectrum in the era of multi-messenger astronomy - Corsi, Alessandra; Eddins, Avery; Lazio, T. Joseph W.; Murphy, Eric J.; Osten, Rachel A. (Frontiers in Astronomy and Space Sciences, 2024)
Compact objects across the mass spectrum–from neutron stars to supermassive black holes–are progenitors and/or central engines for some of the most cataclysmic phenomena in the Universe. As such, they are associated with radio emission on a variety of timescales and represent key targets for multi-messenger astronomy. Observations of transients in the radio band can unveil the physics behind their central engines, ejecta, and the properties of their surroundings, crucially complementing information on their progenitors gathered from observations of other messengers (such as gravitational waves and neutrinos). In this contribution, we summarize observational opportunities and challenges ahead in the multi-messenger study of neutron stars and black holes using radio observations. We highlight the specific contribution of current U.S. national radio facilities and discuss expectations for the field focusing on the science that could be enabled by facilities recommended by the 2020 Decadal survey such as the next generation Very Large Array (ngVLA).